THE EFFECT OF DAYAK ONION (ELEUTHERINE PALMIFOLIA) EXTRACT CREAM APPLICATION ON SERUM INTERLEUKIN-6 LEVELS: AN EXPERIMENTAL STUDY IN UVB-INDUCED MALE WISTAR RATS - Armadina Fitra Choirunnisa; Liza Afriliana; Galih Sari Damayanti; Widyawati Widyawati (Diponegoro International Medical Journal, 2025)
Background: Indonesia receives intense ultraviolet B (UVB) exposure. Prolonged exposure to (UVB) radiation is a major environmental factor contributing to oxidative stress and skin inflammation through the overproduction of reactive oxygen species (ROS) and subsequent upregulation of pro-inflammatory cytokines, including interleukin-6 (IL-6). Eleutherine palmifolia, traditionally used in Indonesian herbal medicine, contains abundant flavonoids and phenolic compounds with documented antioxidant and photoprotective properties. Its ability to absorb UV rays and neutralizing ROS suggests potential efficacy as a topical agent for mitigating UVB-induced inflammatory responses. Objective: This study aimed to evaluated the effect of Eleutherine palmifolia extract cream at various concentrations (10%, 15%, 20%) on serum IL-6 levels in UVB-induced male Wistar rats. Methods: A true experimental design with post-test only control group was conducted using 36 male Wistar rats randomly assigned to four groups: control (placebo), P1 (10%), P2 (15%), and P3 (20%). The cream was applied 20 minutes before UVB exposure and again 4 hours after irridation, three times per week for 30 days. Serum IL-6 levels were measured using ELISA. Statistical analysis was performed using Shapiro–Wilk, Levene’s test, one-way ANOVA, and LSD post-hoc test. Results: Mean IL-6 levels (pg/mL): control 1.63; P1 1.59; P2 1.65; P3 1.57. ANOVA indicated a significant differences among groups (p = 0.047). Post-hoc analysis showing a significant difference only between P2 and P3 groups (p = 0.012). Conclusion: The 20% Eleutherine palmifolia cream showed the strongest anti-inflammatory effect, significantly lowering IL-6 compared with 15%, while other group differences were not significant.